Efficiency of stability-oriented institutions: the European case - Capoen, Fabrice; Creel, Jérôme (Paris, 2007)
"Stability-oriented European institutions correspond to the general prescriptions of the ‘new macroeconomics consensus’. This contribution provides an assessment of the pros and cons of these institutions in terms of macro stabilisation and exchange-rate swings drawing on different scenarios. We argue that the institutions which have been associated with the Euro – limits on public deficits and a conservative central bank – have somewhat jeopardized the efficiency of this new exchange-rate regime. Adaptation of institutions is thus needed: either cooperation or coordination may enhance European welfare."